(untitled) (Revista Venezolana de Salud Pública, 2018)
In order to determine the frequency of malnutrition by excess and some associated risk factors, in schoolchildren of fourth and fifth graders from Republican of Costa Rica School and Nuestra Señora de la Paz School of Barquisimeto Lara state, in period September-December 2011, we performed a descriptive, cross-sectional study, we included 180 student whose representatives gave their written informed consent to participate, with non-probability accidental sample. Current nutritional status was determined by Body mass index (BMI) using the table of the World Health Organization (WHO) and a questionnaire was applied. The results indicate that excess weight affects 30% of the students (40.5% of the Republican of Costa Rica School and 10.9% of Nuestra Señora de la Paz School) and females showed higher percentage with 32.1%. In the studied with overweight and obesity found that 66.7% reported consuming fast food and candy more than 5 times per week, 56.3% physical activity less than 1 hour a day and 46.4% television viewing while eating. We conclude that there is a significant frequency of malnutrition by excess in the student of the public institution in relation to the College. Given that the predominant risk factors were the modifiable, the conduct must be directed to education and prevention, to promote healthy lifestyles.